Distant companions : selected papers - Sicking, C. M. J. (Mnemosyne, Supplements, 1998)
This volume contains fourteen papers on Greek literature, historiography and philosophy. Its titles seeks to bring out the author's intention to explore the consequences of the paradox that goes with interpreting messages that were never meant to be heard by us, but are nevertheless widely believed to be significant to our understanding of our own historical situation: only by conscientiously measuring the distance that separates us from the Greeks may we hope to avoid the risk of conforming them to current standards and beliefs, and of throwing away in the process both the possibility to understand them and the relevance such an understanding may have to our own ideas and prejudices. Two papers on the history of classical scholarship discuss various ways in which classicists have handled this paradox.